IMPROVISING THE COMPETITIVENESS OF MICROENTERPRISES IN THE BRUNCA REGION OF COSTA RICA - Chaves Núñez, Manuel (2013)
Through a diagnostic of competitive capabilities of small companies in the Brunca Region of Costa Rica, we discover limitations in the knowledge that business owners have. However, a combined process of training and monitoring can achieve to reverse the situation faced by these entrepreneurs and improve aptitudes that allow them to compete in an economic system increasingly demanding.